1994
DOI: 10.1104/pp.104.2.699
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Monoclonal Antibodies against Plant Cell-Wall Polysaccharides (I. Characterization of a Monoclonal Antibody to a Terminal [alpha]-(1->2)-Linked Fucosyl-Containing Epitope

Abstract: Monoclonal antibodies (McAbs) generated against rhamnogalacturonan I (RC-I) purified from suspension-cultured sycamore maple (Acer pseudoplafanus) cells fall into three recognition groups. Four McAbs (group I) recognize an epitope that appears to be immunodominant and is present on RC-I from maize and sycamore maple, pectin and polygalacturonic acid from citrus, gum tragacanth, and membrane glycoproteins from suspension-cultured cells of maize, tobacco, parsley, bean, and sycamore maple. A second set of McAbs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
162
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 54 publications
3
162
0
1
Order By: Relevance
“…S9B) and the xth31-1/xth32-1 mutant (Supplemental Fig. S9B) using the Complex Carbohydrate Research Center-Monoclonal1 (CCRC-M1) antibody, which recognizes a(1-2)-linked fucosyl residues present in xyloglucan and rhamnogalacturonan-I (Puhlmann et al, 1994), revealed no significant differences in microscopic cell wall composition in the mutant line. CCRC-M1 staining was observed throughout the roots, including the root hairs, except at the root tip, similar to earlier reports (Freshour et al, 1996).…”
Section: Rootsmentioning
confidence: 99%
“…S9B) and the xth31-1/xth32-1 mutant (Supplemental Fig. S9B) using the Complex Carbohydrate Research Center-Monoclonal1 (CCRC-M1) antibody, which recognizes a(1-2)-linked fucosyl residues present in xyloglucan and rhamnogalacturonan-I (Puhlmann et al, 1994), revealed no significant differences in microscopic cell wall composition in the mutant line. CCRC-M1 staining was observed throughout the roots, including the root hairs, except at the root tip, similar to earlier reports (Freshour et al, 1996).…”
Section: Rootsmentioning
confidence: 99%
“…1, D-G). These include xyloglucan epitopes, as revealed by the monoclonal antibodies (mAbs) LM15 (Marcus et al, 2008) and CCRCM1 (Puhlmann et al, 1994;Fig. 1, D and E), and pectins including homogalacturonan and xylogalacturonan, as revealed by the mAbs LM19 (Verhertbruggen et al, 2009) and LM8 (Willats et al, 2004), respectively ( Fig.…”
Section: Characterization Of Flax Root Border-like Cells and Their Cementioning
confidence: 99%
“…The monoclonal antibodies specific for cell wall polysaccharides used in this study were LM15 (Marcus et al, 2008), CCRC-M1 (Puhlmann et al, 1994), LM19 (Verhertbruggen et al, 2009), LM8 (Willats et al, 2004), and LM1 (Smallwood et al, 1995). Roots were fixed for 30 min in 4% (w/v) paraformaldehyde in 50 mM PIPES, 1 mM CaCl 2 , pH 7, and immunolabeled according to Willats et al (2001).…”
Section: Immunofluorescence Localization Of Cell Wall Polysaccharide mentioning
confidence: 99%
“…Studies of the temporal, spatial, and developmental dynamics of plant cell-wall glycoconjugates have lagged behind corresponding animal studies because of the more limited collection of monoclonal antibodies against cell-wall carbohydrate epitopes that is available and because of the difficulty in characterizing the epitopes recognized by the available antibodies. Previous studies of plant cell-wall dynamics have focused on cell surface glycoproteins, since arrays of monoclonal antibodies have been generated against two types of such complex glycoconjugates, the arabinogalactan-proteins (Anderson et al, 1984;Brewin et al, 1985;Norman et al, 1986;Villanueva et al, 1986;Hahn et al, 1987;Knox et al, 1989Knox et al, ,1991Pennell et al, 1989Pennell et al, ,1991Horsley et al, 1993;Puhlmann et al, 1994;Kreuger and Van Holst, 1995) and Hyp-rich glycoproteins (Smallwood et al, 1994(Smallwood et al, , 1995Knox et al, 1995). Immunohistochemical studies have documented subcellular (Herman and Lamb, 1992;Rae et al, 1992;Van Aelst and Van Went, 1992;Horsley et al, 1993;Sherrier and VandenBosch, 1994) and cell-type-specific (Knox et al, ,1991Stacey et al, 1990;Van Aelst and Van Went, 1992;Benfey et al, 1993;Schindler et al, 1995) distribution of arabinogalactan epitopes.…”
mentioning
confidence: 99%
“…We have generated a small pane1 of monoclonal antibodies that recognize carbohydrate epitopes in plant cell-wall polysaccharides (Puhlmann et al, 1994). The epitopes of two of these antibodies were characterized in some detail.…”
mentioning
confidence: 99%